2022
DOI: 10.1021/acsami.2c03509
|View full text |Cite
|
Sign up to set email alerts
|

Porous Nanostructured Composite Film for Visible-to-Infrared Camouflage with Thermal Management

Abstract: Progressive advancement in modern detection technologies entails multispectral compatible camouflage. Previously, infrared camouflage materials, such as photonic crystals and metamaterials, have been developed, but improved multispectral compatibility, easy fabrication, and cost-effectiveness remain a challenge. Here, we report a nanostructured composite film based on oxalate-rich porous alumina (OPA) for visible-to-infrared compatible camouflage and simultaneous thermal management. The nanostructured composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…The manufactured nano antenna was well engineered with W 1 of 551 nm, W 4 of 673 nm, and T d of 100 nm showing a dimensional deviation of ∼20 nm (Figure e,f). The measurement results indicated that the manufactured PSO nano antenna was far superior to the previous reports. ,, In particular, it had broadband emission at 5–8 μm (ε̅ = 0.34), while simultaneously ensured low emission at 3–5 μm (ε̅ = 0.04) and 8–14 μm (ε̅ = 0.02) at a surface temperature of 300 K, which demonstrated good agreement with the simulation results. The certain deviation between the experimental measurements and the simulation was mainly ascribed to the manufacturing deviation.…”
Section: Resultssupporting
confidence: 74%
See 3 more Smart Citations
“…The manufactured nano antenna was well engineered with W 1 of 551 nm, W 4 of 673 nm, and T d of 100 nm showing a dimensional deviation of ∼20 nm (Figure e,f). The measurement results indicated that the manufactured PSO nano antenna was far superior to the previous reports. ,, In particular, it had broadband emission at 5–8 μm (ε̅ = 0.34), while simultaneously ensured low emission at 3–5 μm (ε̅ = 0.04) and 8–14 μm (ε̅ = 0.02) at a surface temperature of 300 K, which demonstrated good agreement with the simulation results. The certain deviation between the experimental measurements and the simulation was mainly ascribed to the manufacturing deviation.…”
Section: Resultssupporting
confidence: 74%
“…Particle Swarm Optimization (PSO), an intelligent optimization algorithm that imitates animal foraging and shows remarkable advantages for multi-parameter design in many fields, , was used to optimize the in-line 2D architectures. The superiority of the PSO in-line 2D nano antenna structure was evidenced by the experiments, which demonstrated maximum 73.6% improvement of IR camouflage compared with the previous literatures. , Additionally, the in-line 2D configuration was expected for high-efficient direct-writing manufacturing, such as femtosecond laser to increase the productivity and tackle the industrial applications. This study coordinated high-performance design and manufacturing purposes, which was essential for developing future functional structures, including but certainly not limited to IR camouflage for hypersonic aircraft engine and funnels of naval ships.…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…[ 330 ] Thermal imaging sensors, which can function in long range surveillance and in complete darkness without any light, are a great tool for spotting possible attackers, it provide a detailed vision relies on tiny temperature change or heat signals, even in smoke and fog. Thermal disparity is quite challenging to conceal, on thermal map, we can obviously observe and spot individuals attempting to camouflage [ 331 ] in along with their environment by hiding behind bushes, in the shadows, or in other ways. The development history of thermal imaging system models reveals considerable improvements made to the practical field over a 40 year period, which made them a valuable tool for defensive system assessments.…”
Section: Applicationsmentioning
confidence: 99%